Climate Change in Fisheries and Aquaculture: Analysis of the Impact Caused by Idai and Kenneth Cyclones in Mozambique - Muhala, Valdemiro; Chicombo, Tomé Francisco; Macate, Isadola Eusebio; Guimarães-Costa, Auryceia; Gundana, Horácio; Malichocho, Celina; Hasimuna, Oliver Jolezya; Remédio, António; Maulu, Sahya; Cuamba, Lucinda; Bessa-Silva, Adam Rick; Sampaio, Iracilda (Frontiers in Sustainable Food Systems, 2021)
Fisheries and Aquaculture are among the most popular activities in coastal regions of the world. In addition, both correspond to high-risk activities within a climate change context as they are vulnerable to environmental changes that threaten the socio-economic sustainability of the fishing communities that depend on fish for food security and income generation. In 2019, the central part of Mozambique was hit by two unprecedented cyclones: Idai and Kenneth that killed over 600 people and left nearly 2.2 million people in need of urgent assistance. The aim of the present study was to investigate the impacts these cyclones had on fisheries and aquaculture in the provinces of Sofala and Zambézia in Mozambique. The study further seeks to propose strategies that could be adopted by the communities to minimize the risks in the future. For the construction of the database, both secondary and primary data collection approaches were used to characterize the cyclone events. Secondary data was collected through sector reports and previously published articles, while primary data was collected through interviews with fishers, sector employees, and aquaculture producers in the affacted provinces. The results revealed that these natural events had both a direct and indirect impact on fishing, as they affected more than 1,440 fishermen that lost 590 vessels, 1800 fishing gear, and 67 boat engines in Sofala province. In Zambézia province, aquaculture producers lost 169 fish ponds, 2 cages, and 606,000 lost fry, while in Sofala province, 58 fish tanks, 204 cages, and 257,500 fish fry were lost. Overall, our study reveals the vulnerability of fisheries and aquaculture to extreme events paticularly the cyclones in Mozambique. Lack of knowledge regarding climate change, advanced preventive measures, and poor adaptive capacity makes the sectors more vulnerable to disasters. Therefore, it is recommended to improve awareness programs, introduce measures and policies that promote resilience and optimum adaptive efficiency.